2009
DOI: 10.5713/ajas.2010.70630
|View full text |Cite
|
Sign up to set email alerts
|

Spray Dried Animal Plasma as an Alternative to Antibiotics in Weanling Pigs - A Review -

Abstract: Piglet health at weaning is compromised due to several stress factors. Following the ban of antibiotic growth promoters new alternatives are required to control these problems. This paper reviews the evidence available for the use of spray dried animal plasma (SDAP) as an alternative to antibiotics in weaning pigs. Data from 75 trials in 43 publications involving over 12,000 piglets (mean values) have been used to calculate the performance responses of piglets according to several factors including SDAP origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
139
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 124 publications
(151 citation statements)
references
References 66 publications
10
139
0
2
Order By: Relevance
“…Diversos estudos (bosi et al, 2004;camPbELL et al, 2010;torraLLardona, 2010) relataram que a resposta no desempenho dos animais com o uso de PSD é significantemente maior em situações de maior desafio sanitário, como em granjas onde estão alojados animais acometidos pelo circovírus, Escherichia coli patogênicas e Staphylococcus aureus.…”
Section: Resultsunclassified
“…Diversos estudos (bosi et al, 2004;camPbELL et al, 2010;torraLLardona, 2010) relataram que a resposta no desempenho dos animais com o uso de PSD é significantemente maior em situações de maior desafio sanitário, como em granjas onde estão alojados animais acometidos pelo circovírus, Escherichia coli patogênicas e Staphylococcus aureus.…”
Section: Resultsunclassified
“…Hansen et al (2) also demonstrated that pigs previously fed SDPP had greater feed intake and poorer feed efficiency (P < 0.05). Therefore, insufficient dietary methionine may have limited pig performance in diets containing SDPP (3,24).…”
Section: Discussionmentioning
confidence: 99%
“…Use of animal proteins during the immediate post-weaning period is, therefore, widely recommended. In particular, use of spray-dried plasma protein in diets fed to newly weaned pigs appears to offer some protection against enteric diseases and diarrhea as recently reviewed (van Dijk et al 2001;Pettigrew 2006;Torrallardona 2010). …”
Section: Use Of Low-protein Dietsmentioning
confidence: 99%